Appendix A: Strategic Plan for Quail Management and Research in the United States: Introduction and Background - Leonard A. Brennan (National Quail Symposium Proceedings, 2017)
I assessed the current, broad-scale status of populations, research, and management for 6 species of quail in the U.S., and used this information as an introduction, background, and justification for a national strategic planning effort for quail management and research. Long-term (1960-89) trends determined from Christmas Bird Count data indicate that California quail (Callipepla californica), northern bobwhite (Colinus virginianus), and scaled quail (Callipepla squamata) populations have undergone (P < 0.05) declines. Geographic distribution of mountain quail (Oreortyx pictus) has contracted dramatically in the northeastern portion of this quail's range. Neither Gambel's (C. gambelii) nor Montezuma quail (Cyrtonyx montezumae) showed evidence of long-term increases or decreases. Wildlife professionals have apparently paid scant attention to quail in the U.S. during the past 10 years. A recent survey of Wildlife Review indicated <0.2% of the publications pertained to quail. During 1990, < 1.0% of Federal Aid in Wildlife Restoration funds were allocated to quail-related projects. Habitat management by the private sector is apparently having little broad-scale impact on bobwhite populations. Contemporary quail management efforts in the U.S. are clearly in the doldrums and in dire need of leadership from professionals with a creative vision for solving problems caused by changing land-use practices. These factors point to a critical need for a national strategic planning effort to develop a comprehensive, coordinated program for quail management and research. An outline of the structure of the Strategic Planning Workshop that was held at Quail III is provided. Specific management and research problems and associated strategies for solving them are available in Issues and Strategies, which follows (page 181).
Keywords: California quail; Callipepla californica; C. gambelii; C. squamata; Christmas Bird Counts; Colinus virginianus; Cyrtonyx montezumae; Federal Aid in Wildlife Restoration; Gambel' s quail; literature; management; Montezuma quail; mountain quail; northern bobwhite; Oreortyx pictus; population trends; scaled quail